Analysis of Criminal Sentences Against Perpetrators of Criminal Acts of Theft with Aggravating Criminal Case Study Decision Number: 208/Pid.B/2024/PN Jap - Alfarizi Lubis, Muhammad Fathur; Mashdurohatun, Anis (Jurnal Hukum Khaira Ummah, 2025)
The crime of theft is one form of crime that often occurs in society and has a significant impact, both for victims and perpetrators. In the context of law, theft is not only seen from the aspect of its criminality, but also from the broader perspective of justice. In Indonesia, Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia states that "the State of Indonesia is a state of law", which means that all actions, including law enforcement against criminal acts, must be based on law and uphold the principle of justice. In addition, Pancasila as the foundation of the state is an important foundation in assessing and analyzing various legal actions, including the crime of theft. The approach method used in this study is the normative legal approach. The normative legal approach is a legal research conducted by examining library materials or secondary data as basic materials for research by conducting a search for regulations and literature related to the problems being studied. 1. The application of legal sanctions against perpetrators of the crime of theft in Decision Number 208/Pid.B/2024/PN Jap has fulfilled the elements of Article 363 paragraph (1) 3 of the Criminal Code normatively, namely theft committed at night in a house or closed yard. The court sentenced the defendant to two years in prison, which legally complies with the provisions of applicable positive criminal law. 2. The judge's considerations in making a verdict are still oriented towards legal-formal justice, without explicitly considering the social, economic, or background aspects of the defendant. This shows that the judge's considerations do not yet reflect the values of substantive justice upheld by Pancasila, especially the second principle "Just and civilized humanity" and the fifth principle "Social justice for all Indonesian people". 3. The punishment of perpetrators of aggravated theft should be based on Pancasila justice, namely by considering the humanitarian aspect, the balance between victim protection and perpetrator rehabilitation, and an orientation towards social development. An approach that only emphasizes the deterrent effect through imprisonment is not enough to realize holistic social justice.